Pengenalan Dan Pengolahan Tumbuhan Obat Bagi Masyarakat Di Desa Banjar Agung Udik Kabupaten Tanggamus - Yulianty; Endang Nurcahyani; Dzul Fithria Mumtazah; Lili Chrisnawati (CV. Multi Kreasi Media, 2024)
Medicinal plants are plants that are used to treat a disease. Along with the progress of the era, the use of medicinal plants began to shift by using chemical-based drugs. Although some use traditional medicine, there are some traditional medicines that have additional medicinal chemicals. This can cause health problems if used for a long period of time. Based on observations in Banjar Agung Udik Village, many people recognize medicinal plants around the house. But to use and process them into medicinal plants, many people do not use them again to overcome a disease. Therefore, knowledge about the introduction and processing of medicinal plants that are good and correct. The hope of this Community Service activity is to increase the knowledge and skills of the community in using medicinal plants and processing them properly in overcoming an illness. Increased understanding occurred in this activity, namely with the results of the pre-test average of 86.67 and the post-test average of 98.75. So that there was an increase of 12.08 points.